Contractual modalities in the dual vocational training: prior experience and employability in Spain. Performance of the education inspection - Femenía Millet, Olga (Avances en Supervisión Educativa, 2020)
This article aims to make known the percentage of the type of contractual modality (contract for training and learning or granting of a scholarship) that is formalized to the students of the Dual Vocational Training of the formative cycles of the family of personal image in the companies of the Valencian Community, find out the number of students that at the end of the contract for training and learning and the scholarship is hired in the staff of the company, and finally, know if the action of the education inspection allows Real data on youth employability in the labor market is obtained. To achieve the proposed objectives, an empirical study is conducted where 100 tutors from the Dual Vocational Education centre and 5 education inspectors supervising educational centres of the family of personal image are interviewed. This field work has been carried out between the months of October 2017 and March 2018. From the data obtained it is detected, on the one hand, that the type of student-majority training model that is carried out to the students of Dual Vocational Training during the period that is formed in the company are unpaid work practices, on the other hand, that only 30% of the students who have a contract for training and apprenticeship and scholarship are hired during their practical training and lastly, that the education inspection observes a quite important discrepancy between the number of contracts , scholarships and unpaid work practices planned in the authorization project of the Dual FP with the data that are actually formalized in the collaboration agreement with the company.